Predicting the current and future distribution of Helianthus tuberosus L. in China using the MaxEnt model under climate change scenarios - Liu, Yuying; Zhao, Qijun; Dai, Yanhong; Ren, Yanjing; Zhao, Mengliang (Frontiers in Plant Science, 2026)
IntroductionPredicting the biogeographic shifts of Helianthus tuberosus L. (H. tuberosus) under climate change is critical for its conservation and sustainable cultivation.MethodsWe utilized occurrence records (n=295) and environmental variables to model current and future distributions across China via a hyperparameter-tuned MaxEnt framework under four Shared Socioeconomic Pathways (SSP126–SSP585, 2050s–2090s).ResultsThe model identified land cover (28.7%), vegetation index NDVI (23.7%), and minimum winter temperature (Bio6, 14.7%) as dominant drivers, collectively explaining 92.3% of distribution constraints. Currently, highly suitable habitats (6.03% of China’s area) cluster in Yunnan, Guizhou, and central Jiangxi. Future projections indicate a 20.4% expansion of these habitats in northwest China due to winter warming, while southeastern coastal regions contract by 9.1% under extreme precipitation. The geographic centroid shifts 197- 238 km northwestward.DiscussionThis shift highlights northwest China as a key climate refuge for H. tuberosus. These results prioritize conservation efforts and support strategic cultivation in climate-resilient zones.